THE CURRENT TREND IN KENYA'S TEA INDUSTRY - Dominic Kiprutoh Koros; Clerance Kelefhile Tshelang; Mayamiko Masangano (Socio-Economics/Agribusiness Department, 2023)
The tea industry in Kenya is comparably similar to other production firms – ups and downs surround its operations day in and day out. Several previous research studies have majored in Kenya's tea industry, with the aim of studying what surrounds tea production. In this project, the focus is to establish a concrete comprehension pertaining current status of Kenya’s tea, the global trade of Kenyan-based tea, the impacts of COVID-19 on the tea industry, and the sector’s possible countermeasures. To fully capture the requirements of the study, helpful resources were obtained through rigorous retrieval of data from the Ministry of Agriculture, Tea Board of Kenya Statista, KNBS, and Kenya Tea Development Agency (KTDA) websites. Also, other sources of information that stood to provide relevant data for this purpose were considered eligible for the research study. The key findings obtained from the studied resources established the following: To start with, Kenya is a significant player at the international level regarding the production and exportation of tea products. India, Kenya, China, and Sri Lanka are the four countries dominating the world in the tea industry. Secondly, the current performance of Kenya’s tea has deteriorated. Third, tea production and trade in Kenya have become resilient during the pandemic coronavirus disease 2019 (COVID-19). Lastly, implementing appropriate strategies is required to enhance companies' performance.